ECONOMIC VALUATION OF MORTALITY-RISK REDUCTION: STATED PREFERENCE ESTIMATES FROM THE UNITED STATES AND CANADA. - CHESTNUT, LAURAINE G.; ROWE, ROBERT D.; BREFFLE, WILLIAM S. (Contemporary Economic Policy, 2012)
Two internet-based surveys were conducted with adults aged 35 to 84-885 respondents in the United States and 641 respondents in Canada-to estimate willingness to pay (WTP) for reducing mortality risks through out-of-pocket costs for health-care programs. All respondents were asked a series of choice questions followed by a payment-card question. Causes of death included cancer and heart attack. Levels of annual mortality-risk reduction were 1, 2, and 5 in 10,000. Converted to values of statistical life, results were in the range of $4-5 million (2002 U.S. dollars) for the choice-question results for a 2-in-10,000 annual risk reduction for illness-related mortality. U.S. and Canadian results were similar. The payment-card results were about 50% lower than the choice-question results. WTP to reduce mortality risk was essentially the same for cancer and heart attack. The results showed WTP weakly increasing with age, and no evidence of lower WTP for older adults versus middle-aged adults. ( JEL Q51)